TOC ACH Journal Vol. 10 No.1 April 2023 - Sujaya, I Nengah (ARCHIVE OF COMMUNITY HEALTH, 2023)
Arc. Com. Health  Journal is an official electronic journal (e-journal) published by PSSKM (Bachelor of Public Health Study Program) Faculty of Medicine, Udayana University. This electronic journal can be accessed through: http://ojs.unud.ac.id/index.php/ach. Journal of Arc. Com. Health is published three times a year, namely April, August and December. Arc. Com. Health publishes research results related to public health such as health policy, maternal and child health, environmental health, public health nutrition, occupational health, health promotion, health economics and related basic sciences such as health biotechnology, molecular biology, bioinformatics and genetics, plants, animals, and cells related to public health. Arc. Com. Health also publishes the results of systematic reviews